PERAN MEDIASI KEPUTUSAN PEMBELIAN PADA KUALITAS PRODUK, KEPERCAYAAN DAN KEPUASAN KONSUMEN APLIKASI SHOPEE - Desinta Fiani; Dwi Novitasari (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
The purpose of this study was to determine the effect of product quality and trust on consumer satisfaction with purchashing decisions as an mediating variabel on the Shopee. The population in this study are Shopee users who live in Yogyakarta. The sample of this study are 80 respondents. Data collection techniques through questionnaires that have been tester for validity and reliability. Data analysis using Structural Equation Model (SEM). The result of this study indicate (1) product quality has a negative effect on purchasing decisions. (2) Trust has a positive effect on purchasing decisions. (3) Product quality has a positive effect on consumer satisfaction. (4) Trust has a positive effect on consumer satisfaction. (5) Purchasing decisions has a positive effect on consumer satisfaction. (6) Purchasing decisions does not mediate the effect of product quality on the consumer satisfaction. (7) Purchasing decisions mediates the effect of trust on the consumer satisfaction.